2018
DOI: 10.1136/practneurol-2018-001930
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for people with Parkinson’s: a practical approach

Abstract: Exercise is key to a healthy and productive life. For people with Parkinson's, exercise has reported benefits for controlling motor and non-motor symptoms alongside the use of pharmacological intervention. For example, exercise prolongs independent mobility and improves sleep, mood, memory and quality of life, all further enhanced through socialisation and multidisciplinary team support. Recent research suggests that optimally prescribed exercise programmes following diagnosis may alter neurophysiological proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…In humans, exercise also increased serum BDNF which is known to cross the blood-brain barrier [ 5 ]. Physical activity is also known to prolong independent mobility and improves sleep, mood, memory, and quality of life, all further enhanced through socialization and multidisciplinary team support [ 6 ]. Optimally prescribed exercise program following diagnosis may alter neurophysiological processes, possibly slowing symptoms [ 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…In humans, exercise also increased serum BDNF which is known to cross the blood-brain barrier [ 5 ]. Physical activity is also known to prolong independent mobility and improves sleep, mood, memory, and quality of life, all further enhanced through socialization and multidisciplinary team support [ 6 ]. Optimally prescribed exercise program following diagnosis may alter neurophysiological processes, possibly slowing symptoms [ 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…Positive evidence for physiotherapy is growing, showing beneficial impact on functional activities that involve gait, transfers, and balance [49]. For the PD patient, exercise has reported benefits for controlling motor and nonmotor symptoms, with the use of pharmacological interventions [50]. is umbrella review also shows that PRT has benefits particularly in the early stages of PD, with lowto-moderate impact training exercises.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the importance of exercise as a rehabilitation strategy, in the current health system, there are no specific rehabilitation programmes in public hospitals, patient groups, or organizations for people with PD. It has been suggested that neurologists should identify the types of exercises optimal for PD patients and ensure that the methods are safely and effectively implemented [7]. In order to do so, however, neurologists must have up-to-date, detailed, and quality information on the effects of physical exercise on PD.…”
Section: Introductionmentioning
confidence: 99%